4‐Propargyl‐substituted 1H‐pyrroles induce apoptosis and autophagy via extracellular signal‐regulated signaling pathway in breast cancer. Issue 10 (24th June 2021) - Atmaca, Harika; Ilhan, Suleyman; Yilmaz, Elif Serel; Zora, Metin
Abstract: Novel pyrrole derivatives (PDs) with propargyl units (1 –7 ) were investigated for their anticancer activity on breast cancer cells. The MTT assay was used to assess the cell viability. Morphological changes in human breast cancer cells were visualized under a phase‐contrast microscope. Apoptosis and autophagy were detected using the DNA fragmentation assay and staining by autophagic vacuoles, respectively. The levels of apoptosis‐ and autophagy‐related proteins such as cytochrome c, Bcl‐2, LC3‐I/II were investigated by Western blot analysis. The effect of PDs on the ERK1/2 signaling pathway was investigated using specific inhibitors. All the tested PDs were found to be active in the range of 36.7 ± 0.2 to 459.7 ± 4.2 µM. Compounds 3 and 4 showed cytotoxic activity in breast cancer cells, but were found to be safer with lower cytotoxicity on human nontumorigenic epithelial breast cells. Compound 4 induced apoptosis, whereas compound 3 induced autophagy. Both compounds inhibited the ERK signaling pathway in breast cancer cells. The present study revealed that both synthesized PDs induced different programmed cell death types by inhibiting the ERK signaling pathway in two genotypically different breast cancer cells. Therefore, novel PDs might be promising anticancer agents for breast cancer therapy and further structural modifications of PDs may yield promising anticancer agents. Abstract : Novel pyrrole derivatives with propargyl units (1 –7 ) were evaluated for their anticancer activity on breast cancer cells. Compounds 3 and 4 showed cytotoxic activity in breast cancer cells, but were found to be safer, with lower cytotoxicity, in human nontumorigenic epithelial breast cells. Compound 4 induced apoptosis, whereas compound 3 induced autophagy. Both compounds inhibited the ERK signaling pathway in breast cancer cells.